KAJIAN LITERATUR: INTEGRASI PEMBELAJARAN IPS WARISAN BUDAYA UNTUK PEMBENTUKAN KARAKTER SISWA DI KELAS V SEKOLAH DASAR - Faizatul Hasanah; Nanda Dwi Saharani, May; Dwi Rahmah, Alisyah; Ayu Ramanda Putri, Inessya; Tri Febrianto, Priyono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Basic education plays a crucial role in shaping students' personalities as the primary foundation for nation-building. However, the current advancement of globalization and digitalization has led to a decline in moral values, a diminished sense of nationalism, and a weakening of social interaction among students. Social Studies (IPS) learning, which should help shape social values, still feels impractical, difficult to understand, and less relevant to everyday life. Therefore, innovations in learning are needed that can incorporate values ​​from everyday life, one of which is by utilizing cultural heritage. This study aims to analyze the integration of cultural heritage-based social studies learning in character development for fifth-grade elementary school students. The method used was a qualitative research approach with a literature review approach on 28 selected scientific articles published between 2022 and 2025. Data analysis techniques were carried out through the stages of data reduction, data presentation, and systematic conclusion drawing. The results of the study indicate that integrating cultural heritage in social studies learning can improve students' contextual understanding, strengthen cultural identity, and foster character values ​​such as cooperation, tolerance, and responsibility. Implementation is carried out through the use of local wisdom, folklore, and regional traditions, supported by innovative learning models such as Problem-Based Learning (PBL), Project-Based Learning (PjBL), and the 7E Learning Cycle. This approach has proven effective in increasing student participation, social empathy, and collaboration skills. Therefore, the integration of cultural heritage-based social studies learning is a relevant pedagogical strategy for creating meaningful learning and developing students with character, culture, and adaptability to current developments.